PENGGUNAAN TEKNOLOGI GADGET SEBAGAI MEDIA PEMBELAJARAN PADA ANAK USIA DINI DI RAUDHATUL ATFHAL AL-IKHLAS KOTA SINGKAWANG - Nurhayati Nurhayati; Aslan Aslan; Susilawati Susilawati (CV. Adiba Aisha Amira, 2023)
The development of technology and communication is currently very rapid. The development of technology and communication has had a huge impact on the world of education, not only adults who are familiar with this sophisticated technology and communication, but also influences the development and education of early childhood and one of them is gadgets. The purpose of this study was to obtain information about